Legal Analysis of Murabahah Contracts on Comsumptive Financing in Sharia Banks - Fatimah Salma Azzahra; Azhar Alam; Isman; Ulfatun Wahidatun Nisa (AL-IKTISAB: Journal of Islamic Economic Law, 2026)
The murabahah contract represents the most widely utilized financing mechanism in Islamic banking in Indonesia, especially within consumptive financing, primarily due to its ease of implementation and the certainty of profit margins for financial institutions. Nevertheless, this widespread use gives rise to legal concerns regarding the extent to which murabahah practices substantively comply with both Islamic legal principles and positive law, particularly in terms of ownership arrangements, contractual transparency, and consumer protection. This study aims to analyze the legal position of murabahah contracts in consumptive financing, examine their conformity with the principles of fiqh muamalah and laws and regulations, and assess its implementation from the perspective of maqāṣid al-syarī'ah. This study adopts a normative juridical approach (yuridis normatif) by applying statutory and conceptual approaches, complemented by an analytical framework to evaluate the consistency between legal norms and their practical application. The data were obtained through library research, encompassing Islamic banking legislation, regulations issued by the Financial Services Authority (OJK), DSN-MUI fatwas, and relevant scholarly literature. The results reveal that, despite the strong formal legal standing of murabahah contracts, their implementation still exhibits several substantive inconsistencies. In particular, the study highlights issues concerning the ambiguity of legal ownership of goods by banks prior to resale, the less optimal use of wakalah contracts that may transfer risk to customers, and the reliance on standard agreements that could potentially undermine consumer legal protection. Moreover, when viewed through the lens of maqāṣid al-syarī‘ah, murabahah practices tend to be excessively profit-driven, thereby risking the neglect of fundamental values such as justice (ʿadl) and public welfare (maṣlaḥah). Therefore, strengthening sharia supervision mechanisms and improving contractual implementation are necessary to ensure greater alignment with both Islamic legal principles and the broader objectives of Islamic banking.